(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2021)
This paper presents a study on improving transient voltage stability operating conditions in power systems using flexible alternating current transmission system (FACTS) devices, namely Static var compensators (SVC), aiming at maintaining the voltage oscillations at the system’s buses during the transient regime that accompanies a network disturbance between certain prescribed limits. The integration of SVC devices is done while also pursuing the optimal SVC parameters’ selection and location. The case study contains a comparative analysis of the results of the optimization problem solved using two metaheuristic optimization techniques, namely Grasshopper optimization (GO) and genetic algorithm (GA).